The Association Between Gastric Endoscopic Findings and Histologic Premalignant Lesions in the Iranian Rural Population. Issue 17 (May 2015) - Niknam, Ramin; Manafi, Alireza; Fattahi, Mohammad Reza; Mahmoudi, Laleh; Lim., Yean
<x xml:space="preserve">Abstract</x> Abstract Atrophic gastritis, intestinal metaplasia, and gastric dysplasia are histologic premalignant lesions (PMLs). Correlation between the gastric endoscopic findings and histologic PMLs is not clear. This study was designed to determine the possible association of endoscopic findings and histologic PMLs. Over 28 months gastric endoscopic findings of consecutive rural patients with dyspepsia were categorized into 3 groups: 1—normal, 2—ulcerative with or without concurrent abnormality, 3—abnormal non-ulcerative. Biopsies of antrum and body were taken from all included patients and examined for the presence of histologic PMLs. Any mucosal abnormality was also biopsied. From 7340 evaluated patients, an overall of 1973 patients were included. 55.7% of patients were in group 1; 3.8% in group 2 and 40.5% in group 3. A within sex analysis showed that the majority of male patients were in PMLs subgroup (P < 0.001) likewise in groups 2 and 3 (P < 0.001). The prevalence of histologic PMLs in groups 2 and 3 was significantly higher than group 1 (P < 0:001) but the difference was not significant between groups 2 and 3 (P = 0.484). Mean (±SD) age of patient with PMLs was 50.25 ± 17.71 whereas in patients without PMLs was 41.16 ± 16.48 (P < 0.001). This study has showed that abnormal gastric endoscopic findings, male sex and increased age can be considered as risk factors of the formation of histologic PMLs. Until further investigations we propose that any abnormality on gastric mucosa (ulcerative or non-ulcerative) could be biopsied for the evaluation of probable histologic PMLs especially in old men.